Silicon-carbon composite material, preparation method thereof, pole piece, application and electrochemical device

The silicon-carbon composite material with core-shell structure is prepared through steps such as spray granulation and carbonization, which solves the problem of poor circulation performance of silicon-carbon composite materials in the prior art, and achieves high circulation performance and suitable for large-scale production.

CN119447238APending Publication Date: 2025-02-14SHANGHAI SHANSHAN NEW MATERIAL CO LTD

Patent Information

Application Number
CN202411565919.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-04
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The circulation performance of existing silicon-carbon composite materials is poor and difficult to promote in large-scale applications.

Method used

Silicon-carbon composite materials with core-shell structures are prepared by spray granulation and carbonization treatment, and multi-stage buffer structures are constructed using porous carbon and porous silicon coated with carbon layer to improve electrochemical performance.

Benefits of technology

It has achieved high cycling performance of silicon-carbon composite materials, with a capacity retention rate of 85.4%-90.4%, which is suitable for large-scale production and application.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119447238A_ABST
    Figure CN119447238A_ABST
Patent Text Reader

Abstract

The invention discloses a silicon-carbon composite material, a preparation method thereof, a pole piece, application and an electrochemical device. The preparation method of the silicon-carbon composite material comprises the following steps: S1, carrying out spray granulation on silicon-carbon precursor slurry to obtain a first precursor; wherein the silicon-carbon precursor slurry is obtained by mixing a silicon source, a carbon source, a pore forming agent and a solvent; s2, carrying out carbonization treatment on the first precursor to obtain a second precursor; and S3, carrying out carbon coating on the second precursor to obtain the silicon-carbon composite material. The battery assembled by the silicon-carbon composite material can effectively inhibit volume expansion of silicon in the silicon-carbon composite material, and the cycle performance of the battery is improved. The preparation method of the silicon-carbon composite material is high in adaptability, lower in production cost, safer and capable of achieving large-scale production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a silicon-carbon composite material and a preparation method, a pole piece, an application and an electrochemical device thereof. Background Art

[0002] With the rapid development of the new energy industry, high energy density has become an important goal pursued by the lithium battery industry. At present, commercial negative electrode graphite has approached its theoretical capacity upper limit, and the room for improvement is relatively limited, making it difficult to meet the growing application needs. Among the many potential negative electrode materials, silicon negative electrode has attracted much attention due to its extremely high theoretical capacity (4200mAh / g), low lithium insertion potential and wide sources, and is regarded as a strong candidate for the next generation of negative electrode materials. However, silicon negative electrode faces challenges such as large volume expansion, poor conductivity, and poor cycle stability during its practical application. These problems limit its promotion in large-scale applications.

[0003] In order to overcome these difficulties, researchers have tried to suppress the volume expansion of silicon and improve the cycle stability of silicon-carbon negative electrodes by reducing the size of silicon particles, making them porous, and designing structures. However, although nano-sizing and porosification can help alleviate volume expansion, they will also reduce the tap density of the silicon-carbon negative electrode, thereby affecting its energy density. At the same time, the cost of nano-sizing and porosification is high, which is not conducive to large-scale production. In contrast, micron silicon has a higher compaction density and has shown unique advantages in applications. However, the expansion problem of micron silicon is more serious, and how to solve the expansion of micron silicon has become a difficult problem of concern.

[0004] At present, the treatment of micron silicon is generally carried out by ball milling, etching, coating and other means to improve the expansion performance of micron silicon, so as to enhance the cycle stability of silicon-carbon negative electrode. Chinese patent document CN111244417B discloses a method for preparing a micron silicon-carbon composite negative electrode material with a long cycle life. The patent uses 3-5μm silicon powder as raw material, and obtains a three-dimensional graphene-carbon silicon composite macroscopic body through carbon coating, dispersion, alkaline etching, hydrothermal treatment, dehydration and other steps. The negative electrode has a strong multi-level buffer structure, which makes full use of the etching of micron silicon by alkali to effectively buffer the volume expansion of silicon. At the same time, with the help of the conductivity and flexibility of graphene, the long life of the silicon negative electrode is achieved. The patent realizes the coating of silicon through a single vapor deposition, and it is difficult to ensure the uniformity of the coating, which inevitably affects the electrochemical performance of the silicon-carbon negative electrode. Chinese patent application CN115241426A discloses a micron silicon-carbon composite material for lithium-ion battery negative electrode and its preparation method. The invention mainly uses micron-grade silicon-based materials as raw materials, and uses ball milling and surfactant-assisted methods to form a core-shell structure, which effectively alleviates the volume change of silicon and maintains the stability of the electrode structure. Although this method uses ball milling to grind the micron silicon into a smaller ball, and then coats it to inhibit the volume expansion of silicon, the ball milling process consumes a lot of energy, and it also requires the use of expensive surfactant reagents, which has a large cost problem for large-scale mass production. Summary of the invention

[0005] The technical problem to be solved by the present invention is to overcome the defect of poor cycle performance of silicon-carbon composite materials in the prior art, and provide a silicon-carbon composite material and its preparation method, pole piece, application and electrochemical device. The battery assembled from the silicon-carbon composite material of the present invention can effectively inhibit the volume expansion of silicon and improve the cycle performance of the battery assembled from the silicon-carbon composite material. The preparation method of the silicon-carbon composite material of the present invention has strong adaptability, lower production cost, is safer, and can achieve large-scale production.

[0006] The present invention solves the above technical problems through the following technical solutions:

[0007] The present invention provides a silicon-carbon composite material having a core-shell structure, wherein the core comprises porous carbon and porous silicon coated with a first carbon layer, wherein the porous silicon coated with the first carbon layer is distributed in the pores of the porous carbon; and the shell is a second carbon layer, and the second carbon layer is coated on the surface of the porous carbon.

[0008] In the present invention, the porous carbon may be a conventional black porous solid carbon in the art, preferably obtained by carbonization of pitch. The total pore volume of the porous carbon may be 0.6-1.5 m 3 / g. The specific surface area of ​​the porous carbon can be 1013.4-1920.7m 2 / g, and the average pore size of the porous carbon may be 1.8347-2.8761nm.

[0009] In the present invention, the silicon content of the silicon-carbon composite material may be 20%-45%, such as 38%, 31%, 26%, 42%, 41% or 40%. The silicon content indicates the percentage of the mass of silicon to the mass of the silicon-carbon composite material.

[0010] In the present invention, the carbon content of the silicon-carbon composite material may be 55%-78%, such as 58%, 62%, 69%, 74%, 59% or 60%. The carbon content indicates the percentage of the mass of carbon to the mass of the silicon-carbon composite material.

[0011] In the present invention, D10 of the silicon-carbon composite material may be 3.5-28 μm, for example, 26, 4.1, 4.0, 3.9 or 3.7 μm.

[0012] In the present invention, the D50 of the silicon-carbon composite material may be 5-10 μm, for example, 8.7, 8.6, 8.9, 8.8 or 8.5 μm.

[0013] In the present invention, the D90 of the silicon-carbon composite material may be 17-19 μm, for example, 18.7, 18.2, 18.9 or 18.5 μm.

[0014] In the present invention, the specific surface area of ​​the silicon-carbon composite material can be 2-6m 2 / g, such as 2.4, 5.3, 2.8, 3.9, 4.8, 4.1 or 4.3m 2 / g.

[0015] In the present invention, the tap density of the silicon-carbon composite material can be 0.8-1.06 g / cm 3 , for example 0.84, 0.98, 1.00, 1.01, 1.02, 1.03, 1.05 or 1.00 g / cm 3 .

[0016] In the present invention, the silicon-carbon composite material preferably further comprises a conductive material, and the conductive material is preferably distributed in the pores of the porous carbon.

[0017] The conductive material may be one or more of carbon nanotubes, conductive carbon black, Ketjen black, vapor grown carbon fiber (VGCF) and graphene, such as carbon nanotubes.

[0018] The present invention provides a method for preparing a silicon-carbon composite material, which comprises the following steps:

[0019] S1, spraying and granulating a silicon-carbon precursor slurry to obtain a first precursor; wherein the silicon-carbon precursor slurry is obtained by mixing a silicon source, a carbon source, a pore-forming agent and a solvent;

[0020] S2, carbonizing the first precursor to obtain a second precursor;

[0021] S3, carbon-coating the second precursor to obtain the silicon-carbon composite material.

[0022] In the present invention, the type of the silicon source can be conventional in the art, such as silicon particles.

[0023] In the present invention, the D50 of the silicon source may be 0.5-4 μm, for example, 3 μm. The Dmax of the silicon source may be less than 15 μm, for example, 11.34 μm.

[0024] In the present invention, the type of the carbon source can be conventional in the art, preferably asphalt, such as coal asphalt and / or petroleum asphalt.

[0025] In the present invention, the residual carbon rate of the carbon source is preferably greater than 40%, for example 43.2%. The residual carbon rate of the carbon source can be obtained by testing according to GB / T268-87.

[0026] In the present invention, the coking value of the carbon source may be 35%-62.6%, such as 54.7%. The softening point of the carbon source may be 100-200°C, such as 112°C.

[0027] In the present invention, the pore-forming agent may be a conventional alkaline pore-forming agent in the art, preferably one or more of sodium hydroxide, potassium hydroxide and ammonium hydroxide, such as potassium hydroxide.

[0028] In the present invention, the type of the solvent is preferably ethanol.

[0029] In the present invention, the mass ratio of the pore former to the silicon source may be 1:(0.2-5), preferably 1:(0.25-4.8), for example, 1:1.125, 1:1.025, 1:1.175, 1:0.75, 1:0.5625 or 1:4.5.

[0030] In the present invention, the mass ratio of the carbon source to the pore former may be (0.5-6):1, preferably (0.6-5.8):1, for example, 1.375:1, 1.475:1, 1.325:1, 0.92:1, 0.6875:1, 5.5:1 or 2.25:1.

[0031] In the present invention, in step S1, the mixing step preferably includes: first mixing the silicon source and the solvent, then adding the pore former, and finally adding the carbon source.

[0032] In the process of mixing the silicon source and the solvent, a stirring and dispersing step is preferably performed. The stirring time may be 10-120 min, such as 80 min. The stirring speed may be 500-1500 rpm, such as 1000 rpm.

[0033] In the present invention, the silicon-carbon precursor slurry preferably also includes a conductive material.

[0034] The conductive material may be one or more of carbon nanotubes, conductive carbon black, Ketjen black, vapor grown carbon fiber (VGCF) and graphene, such as carbon nanotubes.

[0035] The amount of the conductive material may be 0.5%-8.5% of the total mass of the silicon source and the carbon source, preferably 1.0%-5.0%, for example 4.5%.

[0036] Wherein, the conductive material is preferably added simultaneously with the pore-forming agent.

[0037] After the carbon source is added, stirring is preferably performed for 1-4 hours, for example 2 hours.

[0038] In the present invention, the amount of the solvent in the silicon-carbon precursor slurry is not limited, and preferably the solid content of the silicon-carbon precursor slurry is controlled at 7.2-42.6%, such as 39.6%, 40.2%, 38.7% or 41.4%. Preferably, the mass ratio of the silicon source to the volume ratio of the solvent is 1:2-1:6, such as 1:4.

[0039] In the present invention, the temperature of the spray granulation may be 250-350°C, for example 300°C.

[0040] In the present invention, the pressure during the spray granulation may be 0.4-0.88 MPa, for example 0.6 MPa.

[0041] In the present invention, the D50 of the first precursor may be 6.5-14.5 μm, for example, 10.3, 10.5 or 10.9 μm.

[0042] In the present invention, the carbonization treatment is preferably carried out under an inert atmosphere, and the inert atmosphere is preferably nitrogen.

[0043] In the present invention, it is preferred that a pre-carbonization step is further included after the spray granulation and before the carbonization treatment.

[0044] The pre-carbonization temperature may be 400-650°C, for example, 550°C. The pre-carbonization time may be 1-3h, for example, 2h. The rate of heating from room temperature to the pre-carbonization temperature may be 0.5-3°C / min, for example, 1°C / min. The rate of heating from the pre-carbonization temperature to the carbonization temperature may be 3-10°C / min, for example, 5°C / min.

[0045] In the present invention, the temperature of the carbonization treatment may be 700-1100° C., such as 850, 900 or 1000° C. The time of the carbonization treatment may be 1-8 hours, such as 4 hours.

[0046] In the present invention, a washing operation is preferably further included after the carbonization treatment and before the carbon coating. The washing operation may be conventional in the art, such as acid washing and / or water washing. The washing temperature may be 40-80°C, such as 60°C. The washing time may be 1-7h, such as 5h. The pH of the system after the washing is preferably 6.5-7.0.

[0047] In the present invention, the D10 of the second precursor is preferably greater than 3.5 μm, such as 3.7, 3.8, 3.9 or 4.0 μm. The D50 of the second precursor is preferably 9±1.5 μm, such as 8.4, 8.5, 8.7, 8.8, 9.0 or 9.1 μm. The D90 of the second precursor is preferably 18.8±1.0 μm, such as 18.5, 18.6, 18.8 or 18.9 μm.

[0048] In the present invention, D10, D50 or D90 of the second precursor is preferably obtained by pulverization. The operation of the pulverization can be conventional in the art, such as processing in an air flow pulverizer. The frequency of the induced draft fan of the air flow pulverizer can be 42-50 Hz, such as 45 Hz. The frequency of the classifying wheel of the air flow pulverizer can be 24-38 Hz, such as 30 Hz. During the pulverization, the feeding frequency can be 8 Hz-15 Hz, such as 10 Hz.

[0049] In the present invention, the carbon coating method can be conventional in the art, such as gas phase coating. The gas phase coating equipment can be conventional in the art, such as a tube furnace.

[0050] In the present invention, the carbon coating temperature may be 900-1100°C, for example 1000°C.

[0051] In the present invention, the carbon coating time is preferably 1-4 hours, such as 3 hours.

[0052] In the present invention, the carbon coating is preferably carried out under an inert atmosphere. The inert atmosphere is preferably nitrogen. The gas flow rate of the inert atmosphere is preferably 5-50 mL / min, such as 20 mL / min.

[0053] In the present invention, the carbon source for the carbon coating may be one or more of acetylene, methane, carbon monoxide, ethylene, propylene, butene, benzene and toluene, such as methane.

[0054] In the present invention, during the carbon coating, the gas flow rate of the carbon source may be 5-30 L / min, for example, 20 L / min.

[0055] In the present invention, during the carbon coating, the volume percentage of the carbon source can be 30%-70%, preferably 40%-60%, for example 50%. The volume percentage indicates the percentage of the volume of the carbon source to the total volume of the gas in the system during the carbon coating.

[0056] The present invention also provides a silicon-carbon composite material, which is prepared by the preparation method as described above.

[0057] The present invention also provides a pole piece, which comprises the silicon-carbon composite material as described above.

[0058] The present invention also provides an application of the pole piece as described above in the field of electrochemical devices.

[0059] The present invention also provides an electrochemical device, which comprises the pole piece as described above.

[0060] In the present invention, the electrochemical device is preferably a battery.

[0061] On the basis of being in accordance with the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.

[0062] The reagents and raw materials used in the present invention are commercially available.

[0063] The positive and progressive effects of the present invention are:

[0064] (1) In the present invention, a silicon source, a carbon source, a pore-forming agent and a solvent are used as raw materials, and a first precursor with a specific particle size distribution is prepared through a process of liquid phase dispersion homogenization and spray granulation; the etching effect of the pore-forming agent in the carbonization process is then used to achieve in-situ etching of the silicon source and the carbon source, and the component characteristics of the carbon source are further used to achieve a primary coating of the silicon source to construct a second precursor with a multi-level buffer structure, and finally, after carbon coating, a secondary coating of the silicon source is achieved, and finally a silicon-carbon composite material is obtained.

[0065] (2) The silicon-carbon composite material prepared by the present invention has uniform particle size distribution and moderate specific surface area; the half-cell assembled from the silicon-carbon composite material has better electrochemical performance, for example, the capacity can reach 1342-2094mAh / g, the first efficiency reaches 90.2%-93.4%. After 200 cycles, the capacity can still be maintained at 1146-1857mAh / g, and the capacity retention rate is 85.4%-90.4%. BRIEF DESCRIPTION OF THE DRAWINGS

[0066] Figure 1 This is a SEM image of the silicon-carbon composite material obtained in Example 1.

[0067] Figure 2 Schematic diagram of the structure of the silicon-carbon composite material obtained in Examples 1-9.

[0068] Description of reference numerals:

[0069] Porous silicon-1; porous carbon-2; conductive material-3; first carbon layer-4; second carbon layer-5; pores of porous silicon-6; pores of porous carbon-7. DETAILED DESCRIPTION

[0070] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.

[0071] Example 1

[0072] S1. Granulation

[0073] (1) Slurry preparation: Silicon particles with a D50 of 3 μm and a Dmax of 11.34 μm were selected as raw materials and added to an ethanol solution. The volume ratio of ethanol to the mass ratio of silicon particles was 4:1. The mixture was stirred and dispersed by a high-speed stirrer at a stirring speed of 1000 rpm and a stirring time of 80 min, so that the silicon particles were evenly dispersed in the ethanol solution to form a stable suspension. After adding the conductive material carbon nanotubes and the pore-forming agent KOH, stirring was performed for 1 h. The ratios of coal tar (the residual carbon rate of coal tar was 43.2%, the coking value was 54.7%, and the softening point was 112°C) to the total mass of silicon particles were 4.5% and 40%, respectively. Coal tar was then added at a ratio of 55% of the total mass of silicon particles and coal tar, and stirring was performed for 2 h. After completion, a silicon-carbon precursor slurry with a solid content of 39.6% was obtained; wherein the mass ratio of the pore-forming agent to silicon particles was 1:1.125, and the mass ratio of the coal tar to the pore-forming agent was 1.375:1;

[0074] (2): Spray granulation: The obtained silicon-carbon precursor slurry is subjected to spray granulation treatment, and the granulation pressure is set to 0.6 MPa and the temperature is set to 300°C. After screening treatment, the first precursor is obtained, and D50 is 10.5 μm.

[0075] S2: Carbonization treatment

[0076] (1) Pre-carbonization: The obtained first precursor is pre-carbonized under a nitrogen atmosphere, and the temperature rise program is set as follows: pre-carbonization: room temperature to 550°C, the heating rate is 1°C / min, and then the temperature is kept for 2 hours;

[0077] (2) Carbonization treatment: After pre-carbonization, the temperature is raised to 900°C at a rate of 5°C / min for carbonization treatment and kept at this temperature for 4 hours. After the carbonization treatment, acid washing and water washing are performed to finally make the pH of the system 6.5-7. The washing process is: temperature 60°C, time 5h. After washing, drying is performed;

[0078] (3) Crushing treatment: The product obtained in step (2) is crushed by a jet mill to obtain a second precursor. The frequency of the induced draft fan in the jet mill is 45 Hz, the frequency of the classifying wheel is 30 Hz, and the feed frequency is 10 Hz. The D10, D50 and D90 of the obtained second precursor are 3.7 μm, 8.4 μm and 18.5 μm.

[0079] S3: Coating treatment: The second precursor is subjected to gas phase carbon coating in a tubular furnace under a nitrogen atmosphere (nitrogen flow rate is 20 L / min), the methane flow rate is set to 20 L / min, the temperature is controlled to 1000° C., and the gas phase carbon coating is carried out for 3 hours.

[0080] Example 2

[0081] The only difference from Example 1 is that in step S1 (1) the amount of coal tar pitch used in the slurry preparation is 59% of the total mass of silicon particles and coal tar pitch, and the solid content of the silicon-carbon precursor slurry is 40.2%; wherein the mass ratio of the pore-forming agent to the silicon particles is 1:1.025, and the mass ratio of the carbon source to the coal tar pitch is 1.475:1.

[0082] The second precursor obtained in step S2 has D10: 3.7 μm, D50: 9.1 μm, and D90: 18.9 μm.

[0083] Example 3

[0084] The only difference from Example 1 is that in step S1 (1) the amount of coal tar pitch used in the slurry preparation is 53% of the total mass of silicon particles and coal tar pitch, and the solid content of the silicon-carbon precursor slurry is 38.7%; wherein the mass ratio of the pore-forming agent to the silicon particles is 1:1.175, and the mass ratio of the coal tar pitch to the pore-forming agent is 1.325:1.

[0085] The D50 of the first precursor in step S1 is 10.3 μm;

[0086] The second precursor obtained in step S2 has D10: 3.8 μm, D50: 9.0 μm, and D90: 18.8 μm.

[0087] Example 4

[0088] The only difference from Example 1 is that in step S1 (1), the amount of pore-forming agent used in the slurry preparation is 60% of the total mass of silicon particles and coal tar, and the solid content of the silicon-carbon precursor slurry is 41.4%; wherein the mass ratio of the pore-forming agent to the silicon particles is 1:0.75, and the mass ratio of the coal tar to the pore-forming agent is 0.92:1.

[0089] The D50 of the first precursor in step S1 is 10.9 μm;

[0090] The second precursor obtained in step S2 has D10: 4.0 μm, D5: 8.8 μm, and D90: 18.6 μm.

[0091] Example 5

[0092] The only difference from Example 1 is that in step S1 (1), the amount of pore-forming agent used in the slurry preparation is 80% of the total mass of silicon particles and coal tar, and the solid content of the silicon-carbon precursor slurry is 38.9%; wherein the mass ratio of the pore-forming agent to the silicon particles is 1:0.5625, and the mass ratio of the coal tar to the pore-forming agent is 0.6875:1.

[0093] The D50 of the first precursor in step S1 is 10.9 μm;

[0094] The second precursor obtained in step S2 has D10: 3.7 μm, D5: 8.5 μm, and D90: 18.9 μm.

[0095] Example 6

[0096] The only difference from Example 1 is that the specific steps of the carbonization treatment in step S2 are:

[0097] (1) Pre-carbonization: The obtained first precursor is pre-carbonized under a nitrogen atmosphere, and the temperature rise program is set as follows: pre-carbonization: room temperature to 450°C, the heating rate is 1°C / min, and then the temperature is kept for 3 hours;

[0098] (2) Carbonization treatment: After pre-carbonization, the temperature is raised to 850°C at a rate of 5°C / min for carbonization treatment and kept at this temperature for 4 hours. After the carbonization treatment, acid washing and water washing are performed to finally make the pH of the system 6.5-7. The washing process is: temperature 60°C, time 5h. After washing, drying is performed;

[0099] (3) Crushing treatment: The product obtained in step (2) is crushed by a jet mill to obtain a second precursor. The frequency of the induced draft fan in the jet mill is 45 Hz, the frequency of the classifying wheel is 30 Hz, and the feed frequency is 10 Hz. The D10, D5 and D90 of the obtained second precursor are 3.9 μm, 8.7 μm and 18.6 μm.

[0100] Example 7

[0101] The only difference from Example 1 is:

[0102] In step S1 (1), the amount of the pore former used in the slurry preparation is 10% of the total mass of the silicon particles and the coal tar pitch; the solid content of the silicon-carbon precursor slurry is 39.6%, wherein the mass ratio of the pore former to the silicon particles is 1:4.5, and the mass ratio of the coal tar pitch to the pore former is 5.5:1;

[0103] The step (2) of carbonization treatment in step S2 is: after pre-carbonization, the temperature is raised to 1000°C at a rate of 5°C / min for carbonization treatment, and the temperature is kept for 4 hours. After the carbonization treatment is completed, acid washing and water washing are performed to finally make the pH of the system 6.5-7. The washing process is: temperature 60°C, time 5h. After washing, drying is performed.

[0104] The second precursor obtained in step S2 has D10: 3.9 μm, D50: 8.7 μm, and D90: 18.9 μm.

[0105] Example 8

[0106] The only difference from Example 1 is:

[0107] In step S1 (1), the amount of coal tar pitch used in the slurry preparation is 90% of the total mass of silicon particles and coal tar pitch, wherein the mass ratio of the pore-forming agent to the silicon particles is 1:0.25, and the mass ratio of the coal tar pitch to the pore-forming agent is 2.25:1;

[0108] The specific steps of the carbonization treatment in step S2 are:

[0109] (1) Pre-carbonization: The obtained first precursor is pre-carbonized in a nitrogen atmosphere, and the temperature rise program is set as follows: pre-carbonization: room temperature to 600°C, the heating rate is 1°C / min, and then the temperature is kept for 2 hours;

[0110] (2) Carbonization treatment: After pre-carbonization, the temperature is raised to 1000°C at a rate of 5°C / min for carbonization treatment and kept at this temperature for 4 hours. After the carbonization treatment, acid washing and water washing are performed to finally make the pH of the system 6.5-7. The washing process is: temperature 60°C, time 5h. After washing, drying is performed.

[0111] (3) Crushing treatment: The product obtained in step (2) is crushed by a jet mill to obtain a second precursor. The frequency of the induced draft fan in the jet mill is 45 Hz, the frequency of the classifying wheel is 30 Hz, and the feed frequency is 10 Hz. The D10, D50 and D90 of the obtained second precursor are 3.9 μm, 8.7 μm and 18.9 μm.

[0112] Example 9

[0113] S1. Granulation

[0114] (1) Slurry preparation: Silicon particles with a D50 of 3 μm and a Dmax of 11.34 μm were selected as raw materials and added to an ethanol solution. The volume ratio of ethanol to the mass ratio of silicon particles was 4:1. The mixture was stirred and dispersed by a high-speed stirrer at a stirring speed of 1000 rpm and a stirring time of 80 min, so that the silicon particles were evenly dispersed in the ethanol solution to form a stable suspension. After adding the pore-forming reagent KOH, the mixture was stirred for 1 h, with a ratio of 40% of the total mass of coal tar and silicon particles. Coal tar was then added, with a ratio of 55% of the total mass of silicon particles and coal tar, and stirred for 2 h. After the mixture was finished, a silicon-carbon precursor slurry with a solid content of 39.6% was obtained; wherein the mass ratio of the pore-forming agent to silicon particles was 1:1.125, and the mass ratio of coal tar to the pore-forming agent was 1.375:1.

[0115] (2) Spray granulation: The obtained silicon-carbon precursor slurry was subjected to spray granulation treatment, and the granulation pressure was set to 0.6 MPa and the temperature was set to 300° C. After screening treatment, the first precursor was obtained, and D50 was 10.5 μm.

[0116] S2: Carbonization treatment

[0117] (1) Pre-carbonization: The obtained first precursor was pre-carbonized in a nitrogen atmosphere, and the temperature program was set as follows: room temperature to 550°C, the heating rate was 1°C / min, and then kept warm for 2 hours;

[0118] (2) Carbonization treatment: After pre-carbonization, the temperature is raised to 900°C at a rate of 5°C / min for carbonization treatment and kept at this temperature for 4 hours. After the carbonization treatment, acid washing and water washing are performed to finally make the pH of the system 6.5-7. The washing process is: temperature 60°C, time 5h. After washing, drying is performed;

[0119] (3) Crushing treatment: The product obtained in step (2) is crushed by a jet mill to obtain a second precursor. The frequency of the induced draft fan in the jet mill is 45 Hz, the frequency of the classifying wheel is 30 Hz, and the feed frequency is 10 Hz. The D10, D50 and D90 of the obtained second precursor are 3.7 μm, 8.4 μm and 18.5 μm.

[0120] S3: Coating treatment: The second precursor and the slurry containing carbon nanotubes (10% solid content) were mixed, dried to remove the solvent, placed in a tube furnace, the methane flow rate was set to 20L / min, the temperature was controlled to 1000°C, and gas phase carbon coating was performed for 3 hours.

[0121] Effect Example 1

[0122] Malvern Master sizer 3000 was used to test D10, D50 and D90 of the silicon-carbon composite material prepared in the above embodiment.

[0123] The tap density of the silicon-carbon composite material prepared in the above embodiment using Dandong Hengrui Instrument HR-D3 equipment.

[0124] The BET test method is as follows: take 1g of the silicon-carbon composite material obtained in the above embodiment, first vacuum pre-treat it at 300°C for 3h, and after the treatment, transfer it to the Mac ASAP2020Plus, add liquid nitrogen to the Dewar flask, put it back on the tester, open the program to set relevant parameters, and then conduct the test.

[0125] Carbon content test method: LECO RC612 multiphase carbon water analyzer was used for testing. The silicon-carbon composite material prepared in the above embodiment was placed in a corundum crucible and placed in the automatic sampler of the instrument. The combustion temperature was set to 1000°C and the carrier gas flow rate to 20L / min in the built-in software of the instrument, and the instrument was started.

[0126] Silicon content test method: The silicon content was tested using Agilent 5800ICP-OES. The silicon-carbon composite material obtained in the above embodiment was pretreated by microwave digestion for 30 minutes. After the treatment, it was transferred to the Agilent5800ICP-OES device, and the argon gas was turned on first, the pressure was adjusted to 0.7MPa, and the argon gas flow rate was set to 16.7ml / L. Then, the parameters were set in the instrument software ICP Analyzer Pro software interface: gas pre-filling time 300s, plasma start time 90S, and pump speed 2ml / min. After the settings were completed, the test was carried out.

[0127] The results are shown in Table 1.

[0128] Table 1

[0129]

[0130] The SEM image of the silicon-carbon composite material obtained in Example 1 is as follows: Figure 1 As shown by Figure 1 It can be seen that the particle size distribution of the silicon-carbon composite material is uniform.

[0131] The schematic diagram of the structure of the silicon-carbon composite material prepared in the embodiment is as follows Figure 2 As shown. Figure 2 It can be seen that the silicon-carbon composite material has a core-shell structure, the core includes porous carbon 2, porous silicon 1 coated with a first carbon layer 4, and a conductive material 3; wherein the porous silicon 1 coated with the first carbon layer 4 and the conductive material 3 are distributed in the pores 7 of the porous carbon 2; the shell is the second carbon layer, and the second carbon layer 5 is coated on the surface of the porous carbon 2.

[0132] Effect Example 2

[0133] The silicon-carbon composite material prepared in the embodiment is mixed with conductive carbon black and polyacrylic acid (PAA) in a mass ratio of 80:15:5, dissolved in deionized water, and stirred at a speed of 1000 rpm for 30 minutes to obtain a slurry. The slurry with a solid content of 39.6% is applied to the copper foil, rolled, and placed in a vacuum drying oven for drying for 24 hours. After drying, the copper foil is cut into 12 mm discs, and the loading amount of the silicon-carbon composite material is 16.8 μg. The positive electrode uses the silicon-carbon composite material prepared in the embodiment, the negative electrode uses a lithium sheet, the diaphragm uses a Celgard2400 polypropylene film, and the electrolyte uses 1 mol / L lithium hexafluorophosphate (purchased from Xinzhoubang). The lithium-ion half-cell is assembled according to the 2032 type battery.

[0134] After the assembled battery was left to rest for 24 hours, it was tested on the Xinwei Battery CT-4000 tester. The test conditions were: capacity and first coulombic efficiency were tested at 0.1C, and cycle performance was tested for 200 cycles at 0.5C.

[0135] The results are shown in Table 2 below.

[0136] Table 2

[0137]

[0138] As shown in Table 1 and Table 2, the silicon content in the silicon-carbon composite material of the present invention is controlled at 26.3%-45.3%, and the carbon content is controlled at 54.6%-73.6%. It has the following technical characteristics: D10 particle size is 3.7-4.1μm, D50 particle size is 8.5-8.9μm, D90 particle size is 18.1-18.9μm, and BET specific surface area is 1.9-5.3m 2 / g, tap density is 0.83-1.06g / cm 3 Its capacity ranges from 1342 to 2094 mAh / g, and the first efficiency reaches 90.2% to 93.4%. After 200 cycles, the capacity can still be maintained at 1146 to 1857 mAh / g, and the capacity retention rate is 85.4% to 90.4%.

[0139] Although the specific embodiments of the present invention are described above, it should be understood by those skilled in the art that this is only for illustration and the protection scope of the present invention is defined by the appended claims. Those skilled in the art may make various changes or modifications to these embodiments without departing from the principles and essence of the present invention, but these changes and modifications all fall within the protection scope of the present invention.

Claims

1. A method for preparing a silicon-carbon composite material, characterized in that: It includes the following steps: S1, spraying and granulating a silicon-carbon precursor slurry to obtain a first precursor; wherein the silicon-carbon precursor slurry is obtained by mixing a silicon source, a carbon source, a pore-forming agent and a solvent; S2, carbonizing the first precursor to obtain a second precursor; S3, carbon-coating the second precursor to obtain the silicon-carbon composite material.

2. The method for preparing the silicon-carbon composite material according to claim 1, characterized in that: The method for preparing the silicon-carbon composite material satisfies one or more of the following conditions (1)-(6): (1) The mass ratio of the pore former to the silicon source is 1:(0.2-5), preferably 1:(0.25-4.8), for example, 1:1.125, 1:1.025, 1:1.175, 1:0.75, 1:0.5625 or 1:4.5; (2) The mass ratio of the carbon source to the pore-forming agent is (0.5-6):1, preferably (0.6-5.8):1, for example, 1.375:1, 1.475:1, 1.325:1, 0.92:1, 0.6875:1, 5.5:1 or 2.25:1; (3) the D50 of the first precursor is 6.5-14.5 μm, for example, 10.3, 10.5 or 10.9 μm; (4) D10 of the second precursor is greater than 3.5 μm, for example, 3.7, 3.8, 3.9 or 4.0 μm; (5) the D50 of the second precursor is 9±1.5 μm, for example, 8.4, 8.5, 8.7, 8.8, 9.0 or 9.1 μm; and, (6) The D90 of the second precursor is 18.8±1.0 μm, for example, 18.5, 18.6, 18.8 or 18.9 μm.

3. The method for preparing the silicon-carbon composite material according to claim 1, characterized in that: The method for preparing the silicon-carbon composite material satisfies one or more of the following conditions (1)-(10): (1) The silicon source is silicon particles; (2) The D50 of the silicon source is 0.5-4 μm, for example 3 μm; (3) The Dmax of the silicon source is less than 15 μm, for example, 11.34 μm; (4) the pore-forming agent is one or more of sodium hydroxide, potassium hydroxide and ammonium hydroxide, such as potassium hydroxide; (5) The carbon source is asphalt, such as coal tar and / or petroleum asphalt; (6) The residual carbon rate of the carbon source is greater than 40%, for example, 43.2%; (7) The coking value of the carbon source is 35%-62.6%, for example 54.7%; (8) The softening point of the carbon source is 100-200°C, for example 112°C; (9) In step S1, the mixing step includes: first mixing the silicon source and the solvent, then adding the pore former, and finally adding the carbon source; and, (10) The silicon-carbon precursor slurry also includes a conductive material; Wherein, the type of the conductive material is preferably one or more of carbon nanotubes, conductive carbon black, Ketjen black, vapor-grown carbon fiber and graphene, such as carbon nanotubes; The amount of the conductive material is preferably 0.5%-8.5% of the total mass of the silicon source and the carbon source, more preferably 1.0%-5.0%, for example 4.5%.

4. The method for preparing the silicon-carbon composite material according to claim 1, characterized in that: The method for preparing the silicon-carbon composite material satisfies one or more of the following conditions (1)-(10): (1) The temperature of the spray granulation is 250-350° C., for example, 300° C.; (2) The pressure of the spray granulation is 0.4-0.88 MPa, for example 0.6 MPa; (3) The carbonization treatment is carried out under an inert atmosphere; the inert atmosphere is preferably nitrogen; (4) a pre-carbonization step is further included after the spray granulation and before the carbonization treatment; The pre-carbonization temperature is preferably 400-650°C, such as 550°C; the pre-carbonization time is preferably 1-3h, such as 2h; The rate of heating from room temperature to the pre-carbonization temperature is preferably 0.5-3°C / min, such as 1°C / min; the rate of heating from the pre-carbonization temperature to the carbonization temperature is preferably 0.5-10°C / min, such as 1 or 5°C / min; (5) The temperature of the carbonization treatment is 700-1100° C., for example, 850, 900 or 1000° C.; (6) The carbonization treatment time is 1-8 hours, for example 2, 3 or 4 hours; (7) The carbon coating temperature is 900-1100° C., for example, 1000° C.; (8) The carbon coating time is 1-4 hours, for example 3 hours; (9) The carbon source during carbon coating is one or more of acetylene, methane, carbon monoxide, ethylene, propylene, butene, benzene and toluene, such as methane; and, (10) During the carbon coating, the volume percentage of the carbon source is 30%-70%, preferably 40%-60%, for example 50%; the volume percentage represents the percentage of the volume of the carbon source to the total volume of the gas in the system during the carbon coating.

5. A silicon-carbon composite material, characterized in that: The silicon-carbon composite material is prepared by the preparation method of any one of claims 1 to 4.

6. A silicon-carbon composite material, characterized in that: It has a core-shell structure, the core includes porous carbon and porous silicon coated with a first carbon layer, wherein the porous silicon coated with the first carbon layer is distributed in the pores of the porous carbon; the shell is a second carbon layer, and the second carbon layer is coated on the surface of the porous carbon.

7. The silicon-carbon composite material according to claim 6, characterized in that: The silicon-carbon composite material satisfies one or more of the following conditions (1)-(8): (1) The silicon content of the silicon-carbon composite material is 20%-45%, for example, 38%, 31%, 26%, 42%, 41% or 40%; the silicon content represents the percentage of the mass of silicon to the mass of the silicon-carbon composite material. (2) The carbon content of the silicon-carbon composite material is 55%-78%, for example, 58%, 62%, 69%, 74%, 59% or 60%; the carbon content represents the percentage of the mass of carbon to the mass of the silicon-carbon composite material; (3) The D10 of the silicon-carbon composite material is 3.5-28 μm, for example, 26, 4.1, 4.0, 3.9 or 3.7 μm; (4) The D50 of the silicon-carbon composite material is 5-10 μm, for example, 8.7, 8.6, 8.9, 8.8 or 8.5 μm; (5) The D90 of the silicon-carbon composite material is 17-19 μm, for example, 18.7, 18.2, 18.9 or 18.5 μm; (6) The specific surface area of ​​the silicon-carbon composite material is 2-6 m 2 / g, such as 2.4, 5.3, 2.8, 3.9, 4.8, 4.1 or 4.3m 2 / g; (7) The tap density of the silicon-carbon composite material is 0.8-1.06 g / cm 3 , for example 0.84, 0.98, 1.00, 1.01, 1.02, 1.03, 1.05 or 1.00 g / cm 3 ; and, (8) The core of the silicon-carbon composite material further includes a conductive material; the conductive material is preferably distributed in the pores of the porous carbon; The type of the conductive material is preferably one or more of carbon nanotubes, conductive carbon black, Ketjen black, vapor-grown carbon fibers and graphene, such as carbon nanotubes.

8. A pole piece, characterized in that: It comprises the silicon-carbon composite material as described in any one of claims 5-7.

9. Use of the electrode piece as claimed in claim 8 in the field of electrochemical devices.

10. An electrochemical device comprising the pole piece according to claim 8.

Citation Information

Patent Citations

  • A method for preparing a micron-sized silicon-carbon composite anode material with long cycle life

    CN111244417B

  • Micron silicon-carbon composite material for negative electrode of lithium ion battery and preparation method of micron silicon-carbon composite material

    CN115241426A

Cited By

  • Silicon-carbon composite material as well as preparation method and application thereof

    CN120637442A

  • A composite carbon-coated silicon-carbon composite material, a preparation method and application thereof

    CN122907614A